BEL1-LIKE HOMEODOMAIN4 regulates chlorophyll accumulation, chloroplast development, and cell wall metabolism in tomato fruit. (3rd June 2020) - Yan, Fang; Gao, Yushuo; Pang, Xiaoqin; Xu, Xin; Zhu, Ning; Chan, Helen; Hu, Guojian; Wu, Mengbo; Yuan, Yujin; Li, Honghai; Zhong, Silin; Hada, Wuriyanghan; et al.
Abstract : BEL1-LIKE HOMEODOMAIN4 regulates chlorophyll accumulation and chloroplast development in tomato via direct inhibition of the expression of SlPPO, SlCHLD, SlPOR, SlCAB s, and TKN2, and it regulates cell wall metabolism via transcriptional regulation of the expression of SlPE and LeSPL-CNR . Abstract: Tomato ( Solanum lycopersicum ) is a model plant for studying fruit development and ripening. In this study, we found that down-regulation of a tomato bell-like homeodomain 4 ( SlBL4 ) resulted in a slightly darker-green fruit phenotype and increased accumulation of starch, fructose, and glucose. Analysis of chlorophyll content and TEM observations was consistent with these phenotypes, indicating that SlBL4 was involved in chlorophyll accumulation and chloroplast formation. Ripened fruit of SlBL4 -RNAi plants had noticeably decreased firmness, larger intercellular spaces, and thinner cell walls than the wild-type. RNA-seq identified differentially expressed genes involved in chlorophyll metabolism, chloroplast development, cell wall metabolism, and carotenoid metabolism. ChIP-seq identified (G/A) GCCCA (A/T/C) and (C/A/T) (C/A/T) AAAAA (G/A/T) (G/A) motifs. SlBL4 directly inhibited the expression of protoporphyrinogen oxidase ( SlPPO ), magnesium chelatase H subunit ( SlCHLD ), pectinesterase ( SlPE ), protochlorophyllide reductase ( SlPOR ), chlorophyll a/b binding protein 3B ( SlCAB -3B), and homeobox protein knotted 2 ( TKN2 ). In contrast, it positively regulated the expression of squamosa promoter binding protein-like colorless non-ripening ( LeSPL-CNR ). Our results indicate that SlBL4 is involved in chlorophyll accumulation, chloroplast development, cell wall metabolism, and the accumulation of carotenoids during tomato fruit ripening, and provide new insights for the transcriptional regulation mechanism of BELL-mediated fruit growth and ripening.